PTSA-catalyzed one-pot synthesis of quinoxalines using DMSO as the oxidant. Issue 18 (16th September 2016) - Zhang, Zeyuan; Xie, Caixia; Feng, Lei; Ma, Chen
ABSTRACT: An efficient p-toluene sulfonic acid–catalyzed, one-pot, two-step oxidative system for cyclization of o-diaminobenzene with 1, 2-diaryl-2-hydroxyethanone to quinoxalines was described. A nontoxic, readily available oxidant, dimethylsulfoxide (DMSO), was applied in this process. A broad range of substrates was applied to this method, and target compounds were obtained with good yields. GRAPHICAL ABSTRACT: